Design and implementation of an ontology-based information technology outsourcing evaluation system using AHP. (1st December 2006) - Chen, Jau-Rong; Chou, Tzu-Chuan; Lin, Yu-Chih
Adopting IT is essentially an organisational innovation process. In particular, recent emphasis on IT adoption has raised the level of interest and concern about IT outsourcing, which is the practice of turning over part or all of an organisation's IT functions to external service providers. However, evaluating IT outsourcing decisions is still problematic. To address this issue, a new evaluation system using the ontology-based approach and analytic hierarchical process is proposed. The proposed system aims to facilitate the selection of appropriate measures and transform the selected criteria into a hierarchical framework that is suitable for conducting subjective comparisons. A prototype system is implemented and shown by an exemplary case. The implications, limitations and future works of the proposed system for the evaluation of IT outsourcing decisions are discussed.